143k views
5 votes
Please help me answer this question: (3x^2y^6)^7

User Tmr
by
5.2k points

2 Answers

2 votes

(3x²2y⁶)⁷ =

= 3⁷x¹⁴2⁷y⁴²

= 6⁷x¹⁴y⁴²

User LuckyLikey
by
4.9k points
0 votes

Answer: 2187x^14y^42

Explanation:

The given expression is

(3x^2y^6)^7

All the terms enclosed in the parenthesis is raised to the power of seven. We would apply the following rule of indices

(a^b)^c = a^ b×c

This rule will be applied to each term in the parenthesis. This means that each term will be simplified separately. It becomes

(3x^2)^7 × (y^6)^7

= [3^7 × (x^2)^7] × (y^6)^7

= 2187 × x^14 × y^42

Each simplified term is brought back together. It becomes

2187x^14y^42

User Pruivo
by
5.4k points